Bats of Upper Paraguay Basin: fauna review and distribution records - Fischer, Erich; Eriksson, Alan; Francisco, Alêny L.; Pulchério-Leite, Atenisi; Santos, Carolina Ferreira; Gonçalves, Fernando; Camargo, George; Graciolli, Gustavo; Carvalho, Luiz Felipe Alves da Cunha; Bordignon, Marcelo Oscar; Silveira, Maurício; Carvalho, Nayara; et al. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The Upper Paraguay Basin (UPB) includes the Pantanal floodplain and surrounding elevated areas that drain into the Paraguay river, a transition region between four major phytophysiognomic domains in South America – Cerrado, Chaco, Amazon, and Atlantic Forest. The regional fauna is poor in endemism, but the central and transitional position on the continent provides an increased richness of vertebrates from different domains, especially regarding the order Chiroptera. Here, we review the bat species recorded in the UPB, and present distribution maps and a brief description of each species, including information on size, form, colour, environments, shelters, feeding habits, and interactions with predators and parasites. We found records of 93 species in seven families – Emballonuridae (3), Noctilionidae (2), Mormoopidae (2), Phyllostomidae (51), Natalidae (1), Molossidae (20), and Vespertilionidae (14). Sixty-six species were recorded in the floodplain and 84 in the surroundings, with 59 species reported in both the floodplain and surroundings. Almost two-thirds of the species (63%) were recorded in five or more localities in the UPB and one-fifth (19%) in a single locality. The bat fauna of the UPB highlights this region’s importance for maintaining bat diversity in South America.